2011
DOI: 10.4149/av_2011_03_267
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of porcine circovirus 2 infection in pig population in Slovakia

Abstract: The prevalence of porcine circovirus 2 (PCV-2) infection in the pig population in Slovakia was investigated. Sera from pigs suspected for post-weaning multisystemic wasting syndrome (PMWS) as well as clinically healthy pigs were tested for viral DNA and specific IgM and IgG antibodies. Pigs (n = 198) were categorized to weaning, grower and fattening ones and sows. The results showed that PCV-2 antibodies were present in 53.4% of PMWS-suspects, in 50.0% of healthy pigs and in 69.0% of sows. In PMWS-suspect grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(9 reference statements)
2
1
0
Order By: Relevance
“…The seroprevalence was more in growers and adult animals. This was in agreement with the earlier reports (Csank et al 2011).…”
Section: Resultssupporting
confidence: 94%
“…The seroprevalence was more in growers and adult animals. This was in agreement with the earlier reports (Csank et al 2011).…”
Section: Resultssupporting
confidence: 94%
“…In our study, specific PCV2 antibodies were found in 74.8% of tested animals, and this result is very similar to the results from some other European countries, such as Spain, with seroprevalence of 72.7% (Rodriguez-Arrioja et al, 2003) and France with 80.2% (Blanchard et al, 2003). Seroprevalence determined in our study is lower compared to the results from Belgium with seroprevalence of 100% (Lefebvre et al, 2008), and higher than the results from Austria with seroprevalence of 60.0% (Schmoll et al, 2008) and Slovakia with 54.0% of animals tested positive (Csank et al, 2011). Seroprevalence determined in this study, however, is lower than in Canada with 82.4% (Liu et al, 2002) and the USA with 80.0% of specimens tested positive (Nawagitgul et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…for South Africa [2], Uganda [39], Slovakia [11], Colombia [32], Japan and the UK [5]. Also, much higher prevalences has been found in Uganda [21] Mozambique [23] and in Taiwan [7] by the PCR.…”
Section: Discussionmentioning
confidence: 99%